Antifungal Properties of Polymyxin B and Its Potentiation of Tetracycline as an Antifungal Agent - Schwartz, S. N. (1972)
High concentrations of polymyxin B inhibited the growth of Candida albicans and Saccharomyces cerevisiae. When these yeasts were incubated with concentrations of polymyxin B too low to affect growth, and were then exposed to tetracycline, protein synthesis was inhibited and at least 99% of the organisms were killed. Neither inhibition of protein synthesis nor cell death occurred in cultures treated with high concentrations of tetracycline alone. We conclude that polymyxin B at high concentrations affects the cell membrane of yeasts, which results in inhibition of growth. At low concentrations, it increases the permeability of the yeast cell membrane to tetracycline, which then inhibits protein synthesis and leads to cell death.